Evaluation of the use of laboratory tests in primary care - Valle, Adriana P. [UNESP]; Boas, Paulo José F. Villas [UNESP]; Bicudo, Wanice W.; Jacinto, Alessandro F. [UNESP] (GN1 Sistemas e Publicacoes, 2016)
Introduction: The evaluation of the use of laboratory tests in primary care can improve the quality of care provided to the population. Objective: To evaluate the laboratory tests in primary health care. Methods: Tutorial groups were set to evaluate the reports of laboratory tests requested at 15 basic health units in the city of Botucatu during a 12-month period. The obtained information was evaluated as to the amount of tests requested per medical consultation and the proportions of tests with abnormal results. Results: The rate of laboratory tests requested in medical consultations is far above the recommended by the Ministry of Health, allowing us to infer that there are many unnecessary requests. The test that more often showed abnormal results was glycated hemoglobin, what indicates a possible inadequate management of diabetic patients. Conclusion: Knowing and monitoring laboratory attention enables health unit managers to enhance effectiveness and rational use of the scarce available resources.
Keywords: Laboratory test; Primary health care